Vocabulary Learning Perceptions and Willingness to Communicate: A Comparison of Two Video Game Genres - Vanamo, Ilari (My University, 2023)
This MA thesis examined the differences in vocabulary leaning perceptions and willingness to communicate (WTC) of players of two video game genres: the players of First Person Shooter (FPS) games, and the players of Massively Multiplayer Online Role-Playing (MMORPG) games. The aim of this thesis was to ascertain which target group of video game-players perceived their genre to be more useful or conducive to incidentally learning vocabulary and how their genre affected their WTC. The data for the comparison were gathered using an anonymous online questionnaire created on the Webropol website. The questionnaire consisted of three sections: the background information section, the WTC section, and the vocabulary section. A total number of 43 participants took part in the questionnaire. This number of participants was adequate to apply quantitative methods to the results of the questionnaire. Questionnaire answers were given simple scores and compared using Microsoft Excel and the IBM SPSS statistics program. In both sections of the questionnaire, the MMORPG group outscored the FPS participant group. An Independent Samples T-test found there to be significant differences (p=.027) in the WTC section, but no significant differences (p=.245) were found in the vocabulary section. Nonetheless, the vocabulary section did provide results that skewed in favour of the MMORPG participants in a similar manner to the WTC section. The results of this thesis indicate that MMORPGs are better suited for these two facets of language learning. While previous research has highlighted the benefits of MMORPGs for language learning, no direct comparison has been made with other video game genres. Future research could focus on comparing additional genres to MMORPGs or different genres.
Keywords: second language acquisition, vocabulary, willingness to communicate, digital video games, MMORPG, FPS, quantitative study.